2015
DOI: 10.1093/nar/gkv423
|View full text |Cite
|
Sign up to set email alerts
|

Signal integration by the CYP1A1 promoter -- a quantitative study

Abstract: Genes involved in detoxification of foreign compounds exhibit complex spatiotemporal expression patterns in liver. Cytochrome P450 1A1 (CYP1A1), for example, is restricted to the pericentral region of liver lobules in response to the interplay between aryl hydrocarbon receptor (AhR) and Wnt/β-catenin signaling pathways. However, the mechanisms by which the two pathways orchestrate gene expression are still poorly understood. With the help of 29 mutant constructs of the human CYP1A1 promoter and a mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Wild-type HepG2 cells are deficient in both previously mentioned receptors. For monitoring AHR activity, a pT81luc-based luciferase reporter system driven by an array of three AHR-binding dioxin response elements from the human CYP1A1 gene promoter was transfected (Schulthess et al, 2015). A plasmid encoding Renilla luciferase under the control of a constitutively active promoter was cotransfected for normalization purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type HepG2 cells are deficient in both previously mentioned receptors. For monitoring AHR activity, a pT81luc-based luciferase reporter system driven by an array of three AHR-binding dioxin response elements from the human CYP1A1 gene promoter was transfected (Schulthess et al, 2015). A plasmid encoding Renilla luciferase under the control of a constitutively active promoter was cotransfected for normalization purposes.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, induction of cytochrome P450 (P450) enzymes by exogenous compounds via the aryl hydrocarbon receptor (AHR), constitutive androstane receptor (CAR), and pregnane X receptor (PXR) has been studied extensively (Honkakoski and Negishi, 2000). In addition to xenobiotic nuclear receptor ligands, endogenous signaling pathways also affect the regulation of hepatic drug metabolism via nuclear receptors [e.g., see Braeuning et al (2009), Braeuning and Schwarz (2010), or Schulthess et al (2015)].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, this was demonstrated by the specific loss of CTNNB1 that encodes β -catenin and leads to a decrease of mCyp1a1 induction by AHR agonists such as 3-methylcholanthrene (3-MC), β -naphthoflavone ( β -NF), and butylated hydroxyanisole. Additionally, it has been observed that maximum mCyp1a1 induction was obtained when β -catenin acted as coactivator of AHR, although this protein also binds to the transcription factor TCF, which has a binding site in mCyp1a1 promoter, suggesting a different mode of action [3234]. Similarly, in rat hepatoma, it has been observed that the interaction between AHR and hypophosphorylated retinoblastoma protein (pRb) aids maximum induction of rat CYP1A1 by 2.3, 7.8 tetrachlorodibenzo-p-dioxin (TCDD); pRb plays an important role in cell cycle control and it has been proposed that it could also act as a coactivator of AHR [35, 36].…”
Section: Upregulation Of Cyp1a1mentioning
confidence: 99%
“…3C), and the same type of predictions are possible for combined RBP knockdowns and combination of RBP knockdown and sequence mutations. Conceptually, the modeling framework resembles thermodynamic models of transcriptional gene regulation (30)(31)(32). However, for the case of splicing, regulation is more complex compared to transcription, as both the regulators (RNAbinding proteins) and the effectors (spliceosomes) show combinatorial binding to multiple sequence elements.…”
Section: Discussionmentioning
confidence: 99%